Propionibacterium (Cutibacterium) granulosum Extracellular DNase BmdE Targeting Propionibacterium (Cutibacterium) acnes Biofilm Matrix, a Novel Inter-Species Competition Mechanism - Bronnec, Vicky; Eilers, Hinnerk; Jahns, Anika C.; Omer, Hélène; Alexeyev, Oleg A. (Frontiers in Cellular and Infection Microbiology, 2022)
Acne vulgaris is the most common dermatological disorder worldwide affecting more than 80% of adolescents and young adults with a global prevalence of 231 million cases in 2019. The involvement of the skin microbiome disbalance in the pathophysiology of acne is recognized, especially regarding the relative abundance and diversity of Propionibacterium acnes a well-known dominant human skin commensal. Biofilms, where bacteria are embedded into a protective polymeric extracellular matrix, are the most prevalent life style for microorganisms. P. acnes and its biofilm-forming ability is believed to be a contributing factor in the development of acne vulgaris, the persistence of the opportunistic pathogen and antibiotic therapy failures. Degradation of the extracellular matrix is one of the strategies used by bacteria to disperse the biofilm of competitors. In this study, we report the identification of an endogenous extracellular nuclease, BmdE, secreted by Propionibacterium granulosum able to degrade P. acnes biofilm both in vivo and in vitro. This, to our knowledge, may represent a novel competitive mechanism between two closely related species in the skin. Antibiotics targeting P. acnes have been the mainstay in acne treatment. Extensive and long-term use of antibiotics has led to the selection and spread of resistant bacteria. The extracellular DNase BmdE may represent a new bio-therapeutical strategy to combat P. acnes biofilm in acne vulgaris.